2015
DOI: 10.1080/14681811.2015.1025947
|View full text |Cite|
|
Sign up to set email alerts
|

‘I learned to be okay with talking about sex and safety’: assessing the efficacy of a theatre-based HIV prevention approach for adolescents in North Carolina

Abstract: Adolescents are at increased risk of HIV and sexually transmitted infections (STIs) in the Southern states of the USA, where rates among youth are higher than in the rest of the nation. This paper reports on findings from a pilot study of an HIV prevention intervention that uses interactive theatre to educate young people about sexual health. The intervention was developed in Los Angeles and adapted for testing in the South of the USA, with its legacy of abstinence-based approaches to sexual health education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…Moreover, peer-education strategies characterized by using actors who resemble participants (i.e., actors are of a similar age, gender, and race of participants) are shown to increase intervention uptake as they are more culturally and developmentally appropriate for adolescents than traditional teaching methods (Lieberman et al, 2012). Previous evaluations of theater-based interventions have shown that adolescents find these approaches more acceptable and memorable than traditional teaching methods (Lieberman et al, 2012; Lightfoot, Taboada, Taggart, Trang, & Burtaine, 2015). The use of theater-based peer education strategies for adolescent HIV and other STIs prevention may be more effective than traditional teaching methods and warrant further evaluation (Joronen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, peer-education strategies characterized by using actors who resemble participants (i.e., actors are of a similar age, gender, and race of participants) are shown to increase intervention uptake as they are more culturally and developmentally appropriate for adolescents than traditional teaching methods (Lieberman et al, 2012). Previous evaluations of theater-based interventions have shown that adolescents find these approaches more acceptable and memorable than traditional teaching methods (Lieberman et al, 2012; Lightfoot, Taboada, Taggart, Trang, & Burtaine, 2015). The use of theater-based peer education strategies for adolescent HIV and other STIs prevention may be more effective than traditional teaching methods and warrant further evaluation (Joronen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…in North Carolina found that high school participants manifested statistically significant changes in HIV knowledge and attitudes towards safe sex and people living with HIV/AIDS (PLWHA), and that high school participants preferred AMP! to a standard health education class (Lightfoot et al, 2015). However, the research team recognized the need for well-designed (i.e., methodologically rigorous) and theory-driven evaluations of theater-based HIV prevention interventions in school settings.…”
Section: Introductionmentioning
confidence: 99%
“…Audiences have typically been university students on their way to a professional qualification or medical personnel already registered with a professional body (Fix et al, 2012;Wasylko & Stickley, 2003). Lay publics with an interest in a particular topic have sometimes been co-creators as well as audiences for such productions (Lightfoot, Taboada, Taggart, Tran, & Burtaine, 2015;Quinlan & Duggleby, 2009). De la Croix et al reported that medical students engaged in arts-related activities felt that this helped them to form a professional identity, to reflect, thus improving self-awareness, to empathise more with patients and to communicate better (de la Croix, Rose, Wildig, & Willson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The instructor trained the undergraduates enrolled in the course (n=10) in interactive theater techniques, and public health graduate students led them in a short course on sexual health and HIV prevention. 5 Beyond the university campus, our collaboration involved two school district administrators who oversaw health programs and curricula. They coordinated logistics with schools, connected us with the teachers to whose students AMP!…”
Section: Introductionmentioning
confidence: 99%